Torque ripple minimization of PMBLDC motor using simple boost inverter - Vengadakrishnan, Krishnakumar; Madhanakkumar, N; Pugazhendiran, P; Bharatiraja, C; Sriramkumar, V (Institute of Advanced Engineering and Science, 2019)
This paper proposes the implementation of simple boost circuit incorporated in inverter fed Brushless DC (BLDC) motor drive to boost the performance of torque. BLDC motor becoming subtle because of its performance. But the motor performance is inferior due to the voltage source inverter fed operation of BLDC motor which initiates torque ripple during commutation. Here the usage of Switched Boost Inverter (SBI) which minimizes the storage elements (passive elements), more active element and introduces shoot through mode during commutation as like Z-source inverter. The analyses of three phase switched boost inverter fed BLDC motor drive have been carried out. The performance of torque almost depends on the stator phase current of the motor. In BLDC motor during commutation interval, one phase loss its exact stator phase current hence it instigate ripple on the torque. The proposed method focuses two intentions to reduce the torque ripple. The first intension is to operate the BLDC motor at 180ᵒ electrical conduction mode, second intension is to introduce the shoot through interval to boost the dc link voltage so as to maintain the stator phase current control which leads to suppress the torque ripple during commutation. The validation of the proposed SBI based BLDC motor control is demonstrated both by MATLAB/Simulink and Field programmable gate array (FPGA) controller-SPARRTAN III processor. The experimental results of the developed SBI based BLDC motor drive is working over a wide speed range with minimal torque ripple compared to the normal PWM based inverter control.